2017
DOI: 10.1177/1367006917741364
|View full text |Cite
|
Sign up to set email alerts
|

Type of early bilingualism and its effect on the acoustic realization of allophonic variants: Early sequential and simultaneous bilinguals

Abstract: Aims and Objectives/Purpose/Research Questions: This study examines the acoustic realization of phrase-initial voiced stops (/b, d, g/) and intervocalic voiced approximants ([β, ð, ɣ]) in Spanish by three groups of Spanish–English bilinguals: simultaneous bilinguals, early sequential bilinguals, and late second language (L2) Spanish learners to investigate if the type of early bilingualism has an effect on the acoustic realization of language-specific phonological processes. Design/Methodology/Approach: Early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 66 publications
3
29
0
Order By: Relevance
“…For work, school, and socializing, however, Spanish is the primary language used. Nevertheless, our results show a trend for early sequential bilinguals to favor glottalization slightly more than simultaneous bilinguals, in line with Amengual's (2019) research, possibly due to having been exposed to only Arabic longer than simultaneous bilinguals. It is expected that the analysis of data from additional Arabic-Spanish bilingual participants will provide further information regarding the impact of bilingual type on glottal stop epenthesis in Puerto Rican Spanish.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…For work, school, and socializing, however, Spanish is the primary language used. Nevertheless, our results show a trend for early sequential bilinguals to favor glottalization slightly more than simultaneous bilinguals, in line with Amengual's (2019) research, possibly due to having been exposed to only Arabic longer than simultaneous bilinguals. It is expected that the analysis of data from additional Arabic-Spanish bilingual participants will provide further information regarding the impact of bilingual type on glottal stop epenthesis in Puerto Rican Spanish.…”
Section: Introductionsupporting
confidence: 91%
“…Regarding our third question, based on previous research (Amengual and Chamorro 2015;Simonet 2011Simonet , 2014, we predicted that language dominance would play a role, with Arabic-dominant participants showing a preference for glottal stop epenthesis to a higher extent than Spanish-dominant participants. Last but not least, for bilingual type we expected early sequential bilinguals to glottalize more than simultaneous bilinguals, and for simultaneous bilinguals to have glottalization rates that fell in the middle of Spanish and Arabic monolinguals, in line with Amengual (2019) and Fowler et al (2008).…”
Section: Dente] (Biondi Assali 1989b)mentioning
confidence: 99%
“…The effects of early, substantial, exposure to a language appear long-lasting and persistent in some cases. For example, Amengual (2017) showed that simultaneous Spanish-English bilinguals and L2 learners of Spanish behaved similarly with respect to stop spirantisation, but speakers who grew up in a monolingual Spanish-speaking household and learned English sequentially behaved differently.…”
Section: Bilingual Acquisition Of Phonetics and Phonologymentioning
confidence: 99%
“…Nevertheless, early linguistic experience does not always result in speech patterns that are akin to those of monolingual speakers. Thus, while heritage language speakers are generally closer in accent to monolinguals in the heritage language than L2 learners (Au, Knightly, Jun & Oh, 2002;Amengual, 2017;Chang, Yao, Haynes & Rhodes, 2011), there are usually differences in their speech patterns (Kupisch et al, 2014;McCarthy, Evans & Mahon, 2013;Oh, Jun, Knightly & Au, 2003). For example, Kupisch et al (2014) showed that heritage language speakers from Germany, France and Italy with exposure to both languages from birth were perceived as foreign-accented from a monolingual native speaker perspective.…”
Section: Early Linguistic Experience Language Use and Dominancementioning
confidence: 99%
“…Changes in first language (L1) and second language (L2) speech may have longterm effects on memory representation, or manifest as fast and transitory (Chang, 2012(Chang, , 2013Sancier & Fowler, 1997). There is evidence that early linguistic experience may be particularly deeply entrenched and can have long-lasting effects (Amengual, 2017;Au, Oh, Knightly, Jun & Romo, 2008;Choi, Cutler & Broersma, 2017;Hyltenstam, Bylund, Abrahammson & Park, 2009); at the same time, it is not immune to change, and may even be overridden in individuals who only became bilingual in adolescence or adulthood (Ahn, Chang, De Keyser & Lee-Ellis, 2017;Bergmann, Nota, Sprenger & Schmid, 2016;de Leeuw, Schmid & Mennen, 2010;de Leeuw, Tusha & Schmid, 2017;de Leeuw, Mennen & Scobbie, 2013;Dmitrieva, Jongman & Sereno, 2010;Mayr, Price, Mennen, 2012;Mennen, 2004).…”
Section: Introductionmentioning
confidence: 99%